2017
DOI: 10.1038/s41598-017-03983-4
|View full text |Cite
|
Sign up to set email alerts
|

ZipA and FtsA* stabilize FtsZ-GDP miniring structures

Abstract: The cytokinetic division ring of Escherichia coli comprises filaments of FtsZ tethered to the membrane by FtsA and ZipA. Previous results suggested that ZipA is a Z-ring stabilizer, since in vitro experiments it is shown that ZipA enhanced FtsZ assembly and caused the filaments to bundles. However, this function of ZipA has been challenged by recent studies. First, ZipA-induced FtsZ bundling was not significant at pH greater than 7. Second, some FtsA mutants, such as FtsA* were able to bypass the need of ZipA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 36 publications
(69 reference statements)
5
36
1
Order By: Relevance
“…Many proteins that bind the CTC of FtsZ have been shown to affect Z-ring structure in vivo and/or affect FtsZ polymer structure in vitro (24,(37)(38)(39). It is unclear if and how these proteins regulate polymerization of FtsZ without interacting directly with the GTPase domain, since the CTC and the GTPase domain are linked by a long unstructured CTL.…”
Section: Discussionmentioning
confidence: 99%
“…Many proteins that bind the CTC of FtsZ have been shown to affect Z-ring structure in vivo and/or affect FtsZ polymer structure in vitro (24,(37)(38)(39). It is unclear if and how these proteins regulate polymerization of FtsZ without interacting directly with the GTPase domain, since the CTC and the GTPase domain are linked by a long unstructured CTL.…”
Section: Discussionmentioning
confidence: 99%
“…The miniring structures of EcFtsZ could also be observed in solution (24,25,48), especially following the addition of ZipA (24), a FtsZ associate protein conserved in only γ -proteobacteria. Similar miniring structures were further observed in the studies of C. crescentus FtsZ when stabilized by the regulator protein FzlA (49) and B. subtilis FtsZ with the addition of ZapA(50).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that FtsZ from E. coli and Pseudomonas aeruginosa could assemble into highly curved short oligomers or miniring structures with the average diameter of 23 nm in the presence of GDP (22)(23)(24)(25). Minirings were especially favored in the presence of ZipA protein (24). We also found highly curved oligomers and miniring structures in the EM images of SyFtsZ pfs during GTP hydrolysis ( Fig.…”
Section: Syftsz Assembled Into Highly Curved Oligomers and Miniring Smentioning
confidence: 99%
“…The increase in fluorescence upon FtsZ assembly was suggested to depend on the number of monomers forming protofilament interfaces and not on the bundling of FtsZ filaments [30][31][32]48]. In the presence of a low concentration of Mg 2+ , the fluorescence intensity of SpnFtsZ increased significantly while the light scattering signal did not the change detectably.…”
Section: Tryptophan Fluorescence As a Probe For Monitoring The Assembmentioning
confidence: 94%
“…Previous studies have extensively examined the assembly characteristics of FtsZs from Escherichia coli, Bacillus subtilis, and Mycobacterium tuberculosis using 90°light scattering, sedimentation assay, and electron microscopy [5,16,[23][24][25][26][27][28][29]. In recent years, tryptophan fluorescence was introduced as a method for monitoring the assembly of FtsZ [30][31][32]. For example, Chen and Erickson prepared several tryptophan mutants of E. coli FtsZ and observed an increase in tryptophan fluorescence in association with the assembly of FtsZ [30].…”
Section: Introductionmentioning
confidence: 99%